Performance evaluation of indigenous floppy sprinkler irrigation system for various crops water management - Sarfraz Hashim (Elsevier, 2021)
Freshwater resources are a natural blessing and vital to life. Water is required in many aspects of life due to its importance in the economy. A Floppy sprinkler system (FSS) is an innovative and unique method for pressurizing irrigation. This method has multiple applications other than traditional methods, which can overcome farmer's issues to adopt the high-efficiency irrigation system. The performance evaluation of two types of floppy sprinklers (imported and indigenous) was the primary objective of this research. Three parameters, application efficiency of the low quarter (AELQ), distribution uniformity (DU), and uniformity coefficient (CU), were evaluated under different levels of riser height and operating pressures. A portable testing bench was designed to determine these parameters and the overall performance of FSS in the agriculture field. The system operated at a different pressure range from 1.5 to 4 bar and riser heights 10ft, 12ft, and 15f for both sprinklers. The results revealed that the system achieved maximum CU, DU, and AELQ at the operating pressure of 2.5 bar and riser height of 10 ft for both types of floppy sprinklers. The corresponding values of CU, DU, and AELQ were 84.5%, 70.7%, and 87.0 % for imported and 82.2%, 67.7%, and 82.5% for indigenous FSS. An overlap simulation model was used to achieve a high percentage of system performance. The results declared that the overlapping between sprinklers should be more than 65% to avoid water losses and minimize the overall system cost.